African American Adherence to COVID-19 Public Health Recommendations - Ray Block Jr; Arthur Berg; Robert P. Lennon; Erin L. Miller; Marcella Nunez-Smith, MD, MHS (SLACK Incorporated, 2020)
By mid-May 2020, most of the United States had been under shelter-in-place orders for several weeks to decrease the spread of coronavirus 2019 (COVID-19). As states begin to lift these orders to reopen the economy, the risk of a resurgence of COVID-19 may be related to the public's voluntary adherence to public health recommendations. We conducted a nationally representative survey of 604 African Americans to generate a risk assessment based on African Americans' compliance with public health recommendations to frequently wash hands, maintain social distancing, avoid touching face, and wear a mask in public. This is, to our knowledge, the most comprehensive study of African Americans and public health adherence specific to COVID-19. The percent of respondents reporting that they always comply with these recommendations was 72%, 67%, 55%, and 65%, respectively. Based on this threshold, African Americans' level of adherence with COVID-19 public health recommendations suggests they may be at high risk of a resurgence of COVID-19 during reopening, and there is an urgent need for targeted, culturally responsive public health messaging that is accessible to communities of color to help address racial disparities in COVID-19 risk.